Removal of Congo red by wollastonite. - Singh V.N.; Mishra G.; Panday K.K. (My University, 2025)
Congo red in waste water from textile, paper and pulp industries can be satisfactorily adsorbed on <53 mu m wollastonite at pH 3.0. -R.A.H.